IAP-antagonists exhibit non-redundant modes of action through differential DIAP1 binding - Zachariou, Anna (Oxford University Press, 2003)
The Drosophila inhibitor of apoptosis protein DIAP1 ensures cell viability by directly inhibiting caspases. In cells destined to die this IAP-mediated inhibition of caspases is overcome by IAP-antagonists. Genetic evidence indicates that IAP-antagonists are non-equivalent and function synergistically to promote apoptosis. Here we provide biochemical evidence for the non-equivalent mode of action of Reaper, Grim, Hid and Jafrac2. We find that these IAP-antagonists display differential and selective binding to specific DIAP1 BIR domains. Consistently, we show that each DIAP1 BIR region associates with distinct caspases. The differential DIAP1 BIR interaction seen both between initiator and effector caspases and within IAP-antagonist family members suggests that different IAP-antagonists inhibit distinct caspases from interacting with DIAP1. Surprisingly, we also find that the caspase-binding residues of XIAP predicted to be strictly conserved in caspase-binding IAPs, are absent in DIAP1. In contrast to XIAP, residues C-terminal to the DIAP1 BIR1 domain are indispensable for caspase association. Our studies on DIAP1 and caspases expose significant differences between DIAP1 and XIAP suggesting that DIAP1 and XIAP inhibit caspases in different ways.